Origami Foldaway Support for Beginners using Image Processing - Gayathri, L; Kumar, Praveen (International Journal of Engineering and Technology, 2018)
Various origami works are distributed as origami books in which a succession of collapsing operations with basic outlines is portrayed. In any case, the origami book reader often will give up the instruction of the book middle, because it is too difficult to understand a way to fold in accordance with the diagrams. This paper proposes an approach to find the next step how to do the folding operation, especially for origami beginners. First, a method of detecting the folding operation based on camera images is been detected by canny edge detection. Then, in order to get the next operation camera image is been compare with the database images with the help of Bag of a visual word and Speed up robust features(SURF) detector to detect the key points by finding out the nearest neighboring distance ration (NNDR) measures to find out the similarities.Â Â